Efektivitas Pelaksanaan Dana Desa di Pulau Sumatera Guna Mendorong Keberhasilan Tujuan Pembangunan Berkelanjutan - Kannitha Alana; Rida Perwita Sari (IPM2KPE, 2023)
This study aims to determine the effect of the effectiveness of implementing village funds on the island of Sumatra on the success of the Sustainable Development Goals, the effectiveness of implementing village funds on the island of Sumatra in 2017-2022, and how the effectiveness of implementing village funds on the island of Sumatra can encourage the success of the Sustainable Development Goals. The research method used in this study is the mix method using WarpPLS 7.0. The population and sample of this study are 131 districts/cities receiving village funds on Sumatra Island in 2017-2022. The results of this study indicate that the effectiveness of village funds influences the success of the Sustainable Development Goals by reducing poverty and hunger rates. This can be seen from the programs implemented using village funds, which can be said to be quite effective in reducing poverty and hunger levels. In conclusion, village funds have an effect on the success of the Sustainable Development Goals by reducing the level of poverty and hunger that occurs in the village. Keywords: Village Funds, Effectiveness, Sustainable Development Goals